ANALYSIS OF ORGANIC CONTENT IN SEAWATER AND SEDIMENT IN THE SOUTH OF BENGKALIS ISLAND RIAU PROVINCE - Hari Winanda; Bintal Amin; Dessy Yoswaty (Asian Journal of Aquatic Sciences, 2023)
Organic matter has an important role in marine ecology and it can be used as an indicator of water fertility. The content of organic matter in the waters in a certain amount can be useful for aquatic biota, but if it exceeds the acceptable threshold for the environment and organisms, it can cause disturbances. The content of organic matter in the waters will increase due to waste from households, agriculture, industry, and organic waste from land that is carried into the waters. Various community and industrial activities both on land and waters in the South of Bengkalis Island can provide input of organic matter in the waters. The method used in this research is a survey method that is carried out directly in the field to collect data and samples which are then analyzed. This study aims to determine the content of organic matter in water and sediment and analyze their possible relationship. The results showed that the organic matter content of the water ranged from 34.36 – 35.96 mg/L and the organic matter content of the sediment ranged from 4.78 – 13.78%. The content of organic matter in the waters has not exceeded the quality standard threshold. The results of a simple linear regression test showed a positive relationship with an R2 value of 0.712, which means that the relationship between the organic matter content of water and sediment is quite strong (71.2%). The types of sediment in the southern waters of Bengkalis Island are the mud type